Herd behavior in Malaysian capital market - Kassim, Salina; Duasa, Jarita (2009)
This study examines the existence of herd behavior among foreign investors in the Malaysian capital market. In methodology, the study analyzes the herd behavior by estimating vector error correction (VECM) model of FPI inflows as well as FPI outflows from/to major investors such as the United States, United Kingdom, Singapore and Hong Kong using quarterly data covering the period of Q1:1991 to Q3:2007.In addition, the variance decompositions and impulse response functions analyses are also adopted for further inferences. The findings provide empirical support on the existence of herd instinct among the foreign investors in the Malaysian capital market. The findings imply that the Malaysian short-term capital market can be volatile due to the herd behavior of the major portfolio investors. It is therefore imperative for Malaysia to take the necessary pre-cautionary measures to ensure that an aggregate reversal in portfolio investment flows would not result in a de-stabilising impact on the economy. This study emphasizes the need to improve market supervision and strengthen the financial structure in efforts to reduce the impact of capital reversal on the Malaysian financial market.